Psychosocial Risk Factors at Work and Sleep Quality in Healthcare Workers – A Cross-Sectional Study - Rohwedder, Luiza Salvador; Triches, Maria Isabel; Sousa, Rosângela Aparecida de; Sato, Tatiana de Oliveira; Mininel, Vivian Aline (Sleep Science, 2024)
Objective To investigate psychosocial factors at work, sleep characteristics, and the correlation between these aspects in healthcare workers.Material and methods A cross-sectional e-survey study was conducted with 125 workers of the Brazilian healthcare system, mostly from the Southeast region, from June 2021 to April 2022. Self-administered questionnaires in Google Forms were used to collect data on personal and occupational characteristics, psychosocial factors (Copenhagen Psychosocial Questionnaire), and sleep quality (Pittsburg Sleep Quality Index). Descriptive statistics and a point biserial correlation test were performed.Results The most reported factors in the risk zone were burnout (86%), stress (81%), emotional demands (75%), work pace (61%), and work-family conflicts (55%). Most participants were classified as poor sleepers (74%), especially nursing technicians/assistants (86%). Burnout (rpb = 0.33) and inadequate predictability (rpb = 0.30) were associated with poor sleep quality.Conclusion Intervention strategies to decrease burnout and increase predictability at work may assist in improving sleep quality among healthcare workers.
Keywords: occupational risks; sleep; occupational health; working conditions; healthcare workers; pyschosocial factors